Modifikasi dan Karakterisasi Titania (M-TiO2) Dengan Doping Ion Logam Transisi Feni dan Cuni - Rilda, Yetria; Arief, Syukri; Dharma, Abdi; Alif, Admin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
Structure and size of titania nanoparticles have been modified with doping the transition metal (FeNiand CuNi) and controlling the calcinations temperature. Gel and M-TiO 2 powder were characterized byFT-IR showed the changed in intensity at 4000-400 cm-1. TG-DTA curve show the weigh of sample wasdecreased with the increasing of temperature 25-800°C. XRD pattern used to identify the titania structureshows the highest intensity of anatase at temperature calcination as 500°C. XRD of FeNi-TiO 2 and CuNi-TiO2 FeNi 10.5-41.9 nm and CuNi 12.1-33.5 converted using Debye-Scherrer’s equation and TEM analysisthe distribution of crystal size as FeNi-TiO2 and CuNi-TiO2 10-15 nm. SEM has shown that morphology ofdifferent surface from the FeNi-TiO 2 and CuNi-TiO 2 at different calcinations temperatures. Titaniacomposition can be determined by EDX analysis give as FeNi-TiO2 1:1, 97.01% and CuNi-TiO2 1:1, 94.63%respectly. The surface area has been determined by BET as FeNi-TiO 2 was 64.38 m2/g and CuNi-TiO2was 40.9 m2/g.